Aristolochia occidentalis (Aristolochiaceae), a new species from the Pentandrae subsection of Colima and Jalsico, Mexico - Santana-Michel, Francisco J.; Lemus Juarez, Sebastian (Instituto de Ecología, A.C., 1996)
Aristolochia occidentalis sp. nov. is described from near the border between the Mexican states of Colima and Jalisco. The species is a member of the subsection Pentandrae Duchartre. It is related to Aristolochia pringlei Rose and Aristolochia bracteosa Duchartre.